A Development Model for Humanistic-Religious Values Education in Character Building among Students of Universitas Pamulang - Mudzakir; Sururin; Taufik Abdillah Syukur; Sapiudin; Desmaliza (Lembaga Bale Literasi, 2026)
This study examines the concept, implementation, effectiveness, and influencing factors of humanistic-religious values education in shaping student character at Universitas Pamulang. The study is based on the importance of strengthening student character through the integration of humanistic and religious values within the higher education environment. The research employed a mixed-methods approach with an explanatory sequential design. The quantitative phase involved a survey of 235 students selected through stratified random sampling using a Likert-scale questionnaire. The data were analyzed using descriptive and inferential statistics with IBM SPSS Statistics software. The qualitative phase was conducted through in-depth interviews, participatory observation, and document analysis using purposive sampling techniques. Qualitative data were analyzed using the Miles, Huberman, and Saldana model, while data validity was ensured through triangulation techniques. The findings indicate that the concept of humanistic-religious values education is effective in developing students’ integrity, tolerance, social responsibility, and religiosity through the integration of these values in accordance with the vision and mission of Universitas Pamulang. In addition, lecturers’ role modeling, student activities, and campus culture play significant roles in reinforcing these values. The implementation is reflected in academic, religious, and institutional practices. Statistical analysis shows a positive and significant influence of humanistic-religious values education on student character formation. Supporting factors include institutional commitment, lecturers’ contributions, the campus environment, and student activities. Meanwhile, the challenges arise from the diversity of students’ backgrounds, social influences, technological developments, and economic as well as academic pressures.